Forskolin Sensitizes Human Acute Myeloid Leukemia Cells to H3K27me2/3 Demethylases GSKJ4 Inhibitor via Protein Kinase A - Illiano, Michela; Conte, Mariarosaria; Sapio, Luigi; Nebbioso, Angela; Spina, Annamaria; Altucci, Lucia; Naviglio, Silvio (Frontiers in Pharmacology, 2018)
Acute myeloid leukemia (AML) is an aggressive hematological malignancy occurring very often in older adults, with poor prognosis depending on both rapid disease progression and drug resistance occurrence. Therefore, new therapeutic approaches are demanded. Epigenetic marks play a relevant role in AML. GSKJ4 is a novel inhibitor of the histone demethylases JMJD3 and UTX. To note GSKJ4 has been recently shown to act as a potent small molecule inhibitor of the proliferation in many cancer cell types. On the other hand, forskolin, a natural cAMP raising compound, used for a long time in traditional medicine and considered safe also in recent studies, is emerging as a very interesting molecule for possible use in cancer therapy. Here, we investigate the effects of forskolin on the sensitivity of human leukemia U937 cells to GSKJ4 through flow cytometry-based assays (cell-cycle progression and cell death), cell number counting and immunoblotting experiments. We provide evidence that forskolin markedly potentiates GSKJ4-induced antiproliferative effects by apoptotic cell death induction, accompanied by a dramatic BCL2 protein down-regulation as well as caspase 3 activation and PARP protein cleavage. Comparable effects are observed with the phosphodiesterase inhibitor IBMX and 8-Br-cAMP analogous, but not by using 8-pCPT-2'-O-Me-cAMP Epac activator. Moreover, the forskolin-induced enhancement of sensitivity to GSKJ4 is counteracted by pre-treatment with Protein Kinase A (PKA) inhibitors. Altogether, our data strongly suggest that forskolin sensitizes U937 cells to GSKJ4 inhibitor via a cAMP/PKA-mediated mechanism. Our findings provide initial evidence of anticancer activity induced by forskolin/GSKJ4 combination in leukemia cells and underline the potential for use of forskolin and GSKJ4 in the development of innovative and effective therapeutic approaches for AML treatment.